Plasmodium Knowlesi Malaria: Assessing the Risk to the British Armed Forces. Issue 4 (1st December 2012) - Roughton, Susanna; Green, AD
Abstract : Plasmodium knowlesi is a zoonosis and is now recognised as the fifth commonly occurring form of human malaria. It is endemic in South East Asia, including some areas previously declared malaria free or at low risk for malaria. The epidemiology of the disease is very different to other forms of malaria which are determined by transmission by anthrophilic mosquitoes from human reservoirs. In contrast Plasmodium knowlesi malaria has a monkey reservoir and disease is transmitted to humans by mosquitoes that normally feed on animals. People become accidentally infected when they enter the ranges of the vector mosquitoes and animal hosts. Improved and novel diagnostic methods have indicated that human disease is much more common than previously thought. Although the greatest disease burden falls on local populations living in endemic areas, visitors entering such zones are also at risk. The changing nature of tourism with deep jungle expeditions being more heavily marketed, and short visits to endemic zones now common, mean that new populations are increasingly recognised as being at risk. One such group are military personnel undergoing jungle training or deployed on Operations. The potential for severe disease in areas previously considered at low risk for malaria means that risk assessment needs to be reviewed, coupled with communication strategies to address prevention of a zoonotic form of the disease. The role of chemoprophylaxis in some specific groups may need to be considered.